Survey of compliance with the cigarettes and other tobacco products act, 2003 at schools in Mangalore, Dakshina Kannada district, Karnataka - Mathias, Jennifer; Jena, Pratap Kumar; Shah, Sanjeev Kumar; Sah, Jay Prakash; Gautam, Koshish Raj; Upadhayay, Abinash (International Journal Of Community Medicine And Public Health, 2019)
Background: Tobacco use is a major problem of public health significance as the tobacco smoking causes a wide range of diseases and adverse health impacts that affect nearly every organ of the body. The COTPA, 2003 i.e., the Indian smoke-free legislation “Prohibition of smoking in Public places” which forbids smoking in public places, including educational institutions. The main objective of this study is to assess the compliance of Section 4 and Section 6(b) of cigarettes and other tobacco products act (COTPA), 2003 in schools, to observe compliance of smoking ban at public places, to observe compliance of display of signboards at prominent places, to observe for direct and indirect evidence of smoking and other tobacco products used in school buildings and premises, to study the availability of tobacco products within 100 yards of school premises. Methods: A cross sectional survey in 100 schools in Dakshina Kannada district using compliance guide developed by partners of Bloomberg School of Public health to reduce tobacco use. Results: In 100 schools, 55 were rural area and 45 from urban area, further division shows government/semi-government schools were 44 and Private schools were 56. Section 4 for the presence of signboard, there is an association between the Management wise schools and presence of signboards (p=0.001), for section 6(b) of COTPA, there is an association between this Section and type of management (p=0.004). Conclusions: The schools depending upon the location show varied compliance towards the law. The Section 6(b) shows better compliance than Section 4.This study will help to address the implementation issues of COTPA.